2020
DOI: 10.1002/bit.27371
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid supplementation for enhancing recombinant protein production in E. coli

Abstract: Recombinant protein production (RPP) in Escherichia coli (E. coli) often induces metabolic burden to the cells that compromise their overall growth and productivity. Amino acid starvation due to RPP is a major contributor of the metabolic burden on the cells and induces global stress response known as a stringent‐like response. In this study, the effect of amino acid supplementation in a chemically defined medium on cellular growth and recombinant pramlintide production was investigated. Based on the consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…Kumar et al also reported that 20 mixed amino acids with chemically defined media increased recombinant peptide production by 40% in E . coli BL21 (DE3) (Kumar et al, 2020). Generally, the addition of amino acids to the growth medium can influence E .…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al also reported that 20 mixed amino acids with chemically defined media increased recombinant peptide production by 40% in E . coli BL21 (DE3) (Kumar et al, 2020). Generally, the addition of amino acids to the growth medium can influence E .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the advantages, some problems are also associated with the production of recombinant proteins in E. coli : the formation of inclusion bodies, the inefficient protein translocation, or the metabolic burden ( Mairhofer et al, 2013 ; Baig et al, 2014 ; Marschall et al, 2017 ). Some current strategies developed to solve these drawbacks are focused on supplementation of essential precursors or use of co-cultures ( Gurramkonda et al, 2018 ; Slouka et al, 2019 ; Chiang et al, 2020 ; Kumar et al, 2020 ; Wang et al, 2020 ). Metabolic burden relates to imbalance suffered by a host cell when a heterologous gene is expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Kurmar et al also reported that 20 mixed amino acids with chemically defined media increased recombinant peptide production by 40% in E. coli BL21 (DE3). [25] Generally, the addition of amino acids to growth medium can influence E. coli protein expression. In rich medium, E. coli cells grow faster, and expression of the majority of the translation apparatus genes is significantly elevated.…”
Section: Discussionmentioning
confidence: 99%